Laparoscopic total nephrectomy for Wilms tumor: Towards new standards of care. Issue 5 (October 2018) - Flores, Paula; Cadario, Martín; Lenz, Yvonne; Cacciavillano, Walter; Galluzzo, Laura; Nestor Paz, Enrique Guillermo; Corbetta, Juan Pablo; Zubizarreta, Pedro
Summary: Introduction: Laparoscopic total nephrectomy (LN) in malignant pediatric tumors remains controversial. For selected patients undergoing pre-operative chemotherapy in referral centers, LN has so far shown comparable results to the standard open technique. Purpose: To describe the inclusion criteria and preliminary results of laparoscopic nephrectomies (LN) for the treatment of unilateral Wilms tumors (WT). Material and methods: Between November 2010 and January 2016, a retrospective study of patients with WT and undergoing pre-operative chemotherapy was performed. Inclusion criteria for candidates for LN were: unilateral tumors without venous invasion and central kidney localization. Tumor size and vascular thrombus were estimated with pre-operative computed tomography (CT) scan. Overall survival and recurrence rates were evaluated. Results: Among 105 patients with WT, 14 underwent LN. Tumor bleeding or the lack of response to chemotherapy were not exclusion criteria. Median tumor volume for the patients undergoing LN was 71.5 cc (range 7–169). Patients with small tumors localized near the renal pole and candidates for nephron sparing surgery (NSS) were excluded. Estimated 5-year overall survival for all patients with WT during this period was 88.7% (88.1–103.1). Two patients underwent conversion. No recurrence or related death was found at a mean 32- month follow-up period. Discussion: Reproducing the steps of the open nephrectomy when performing LN for malignant tumors allowed comparable oncologic results to the conventional procedure. However, upstaging of the tumor was not admissible and has become the main goal when approaching these patients laparoscopically. Preliminary results showed that the incidence of intraoperative rupture and incomplete node sampling were not an issue when comparing LN to open nephrectomy. On the other hand, LN for malignant tumors requires experience in advanced laparoscopy and oncologic surgery. Pre-operative chemotherapy changes the tumor's consistency and this is the key point as to why these patients are amenable to be approached laparoscopically. Lifting the tumor along with the fat to avoid capsule fraction, as well as changing the lens to the lateral port to achieve a correct view for lymph node sampling are some of the considerations when performing LN. Conclusions: Preliminary data suggest that LN for WT is feasible and has promising results in terms of event-free and overall survival. In patients undergoing pre-operative chemotherapy the correct selection for LN is crucial. Following the basic oncological precepts and in experienced centers, LN represents a plausible modality in the care of these patients.